Characterization of a new cosmopolitan genus of trypanosomatid parasites, Obscuromonas gen. nov. (Blastocrithidiinae subfam. nov.) - Lukeš, Julius; Tesařová, Martina; Yurchenko, Vyacheslav; Votýpka, Jan (European journal of protistology, 2021)
The expanding phylogenetic tree of trypanosomatid flagellates (Kinetoplastea: Trypanosomatidae) contains a long-known and phylogenetically well-supported species-rich lineage that was provisionally named as the 'jaculum' clade. Its members were found in representatives of several unrelated families of heteropteran bugs captured in South and Central America, Europe, Africa, and Asia. However, this group resisted introduction into the culture, a needed prerequisite for its proper characterization. Here we describe four new cultivable species, which parasitize various parts of their hosts' intestine, including the thoracic and abdominal part of the midgut, hindgut, and Malpighian tubules. Morphologically, the cultured flagellates vary from relatively short stumpy promastigotes to long slender leptomonad cells. Some species form straphangers (cyst-like amastigotes) both in vivo and in vitro, initially attached to the basal part of the flagellum of the mother cell, from which they subsequently detach. To formally classify this enigmatic monophyletic cosmopolitan clade, we erected Obscuromonas gen. nov., including five species: O. modryi sp. nov. (isolated from the true bug host species Riptortus linearis captured in the Philippines), O. volfi sp. nov. (from Catorhintha selector, Curaçao), O. eliasi sp. nov. (from Graptostethus servus, Papua New Guinea), O. oborniki sp. nov. (from Aspilocoryphus unimaculatus, Madagascar), and O. jaculum comb. nov. (from Nepa cinerea, France). Obscuromonas along with the genus Blastocrithidia belongs to the newly established Blastocrithidiinae subfam. nov.
Keywords: Biodiversity; Cyst-forming trypanosomatids; Parasites; Ultrastructure; Heteroptera; Animals; Culture Techniques; druhová specificita; zvířata; Phylogeny; kultivační techniky; Monoxenous kientoplastids; Species Specificity; Trypanosomatina